Therapeutic interventions of Endoscopic Retrograde Cholangiopancreatography (ERCP): A Tertiary care experience in Bangladesh (Bangladesh Medical Journal, 2026)
Endoscopic retrograde cholangiopancreatography (ERCP) has evolved into a primarily therapeutic procedure for biliary and pancreatic ductal disorders. Despite increasing utilization in Bangladesh, institutional data describing patient characteristics, disease distribution, and procedural interventions remain limited. To evaluate the demographic profile, clinical presentation, indications, and therapeutic interventions among adult patients undergoing ERCP at a tertiary care center in Bangladesh, with comparison between benign and malignant biliary lesions. This retrospective observational study included 150 consecutive adult patients who underwent therapeutic ERCP between January 2022 and January 2024 at Bangladesh Medical University. Data were derived from hospital records. Lesions were categorized as benign or malignant using predefined operational criteria. Continuous variables were analyzed using an independent sample t-test after confirmation of normality by the Shapiro-Wilk test. Categorical variables were compared using chi-square or Fisher’s exact test. The mean age was 50.8 ± 13.5 years (range 18–82), with malignant cases significantly older than benign cases (54.9 ± 13.6 vs 49.1 ± 13.2 years; p = 0.015). Females comprised 50.7% of patients. Benign lesions accounted for 70% and malignant 30%, yielding a benign-to-malignant ratio of 2.3:1. Jaundice was present in 84.7%, and in 100% of malignant cases (p < 0.001). Weight loss (62.2% vs 3.8%) and anorexia (71.1% vs 4.8%) were significantly more common in malignancy (p < 0.001). Choledocholithiasis without cholangitis was the most frequent indication (26.0%). Balloon sweeping was performed in 35.3%, exclusively in benign disease (p < 0.001). Plastic stents were used in 46.0%, predominantly in malignant lesions (66.7%), while self-expanding metal stents (8.7%) were used only in malignancy (p < 0.001). No major procedure-related complications were recorded. In this tertiary center, benign biliary disease, particularly choledocholithiasis, constituted the majority of ERCP indications. Malignancy was strongly associated with advanced age and systemic symptoms. Local epidemiologic characterization may guide resource allocation, training priorities, and therapeutic strategy in Bangladesh.Bangladesh Med J. 2025 Sept; 54(1): 9-16